PEMBELAJARAN FISIKA MENGGUNAKAN BETTER TEACHING AND LEARNING BERKETERAMPILAN PROSES UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA SMP (UPEJ Unnes Physics Education Journal, 2013)
The aim of this research is to determine activities and achievement after was applied Better Teaching and Learning (BTL) process skilled model. Design of this research is Pre-Experiment with One-Group Pretest-Posttest. Sampling was done by purposive sampling. The methods of data collection in this research are documentation, test and observation. Assessment of psychomotor, affective and activities were done by direct observation with observation sheet. Students cognitive are measured by pretest and posttest results. Gain analysis showed that the average of students activities are increased in the high category. Psychomotor and affective are increased in the high category but students cognitive are increased in the medium category. Based on the results as mentioned above, it can be concluded that the application ofÂ BTL process skilled model can increase activities and achievement.